Field Trip and Its Effect on Traditional Ecological Knowledge Literacy During the COVID-19 Pandemic in Rural Primary School - Sumarwati Sumarwati; Edy Suryanto; Slamet Slamet; Mila Anggar Wati (Universitas Pendidikan Ganesha, 2021)
Traditional ecological knowledge (TEK) is the best indigenous practice acquired through centuries of experience in contact with nature. The rural area in Tawangmangu District, located on the slopes of Mount Lawu, Indonesia, is rich in TEK, such as folklore, traditional ceremonies, performing arts, planting systems, and harvesting systems that are starting to be abandoned young. Teaching TEK by bringing students to learning resources allows literacy to occur in cognitive and affective aspects. This study was conducted to determine the effect of teaching through field trips on improving the literacy of local elementary school students in TEK literacy. The study was conducted through a quasi-experimental with pretest-posttest non-equivalent control group design. Learning in the experimental class is carried out outside the home with field trips in small groups (4-6 students), while the control class is carried out using a distance learning system via WhatsApp and radio broadcasts at each student's home. The results show a significant effect of the field trip method on TEK literacy, both in cognitive and affective aspects. d Cohen's analysis shows the effect is quite significant. The level of mastery of TEK material in the field trip class is significantly higher than in the non-field trip class. In addition, students in the field trip class also showed higher pro-environment attitudes than students in the non-field trip class. It is recommended that environmental or local cultural education be held through field visits in small groups to reduce student boredom following distance learning during the pandemic in rural areas.